Glass forming ability, thermal stability and indentation characteristics of Ce60Cu25Al15 - xGax (0 ≤ x ≤ 4) metallic glasses - Singh D.; Mandal R.K.; Srivastava O.N.; Tiwari R.S. (My University, 2025)
Abstract Glass forming ability, thermal stability and indentation characteristics of Ce60Cu25Al15 - xGax (0 ≤ x ≤ 4) metallic glasses have been investigated. Amorphous phase has been confirmed in all these samples with the help of X-ray diffraction (XRD), differential scanning calorimetry (DSC) and transmission electron microscopy (TEM) studies. The compositional dependence of the glass forming ability (GFA) and its correlation with related parameters as well as thermal stability have also been discussed. The load dependent hardness behavior of metallic glasses is reported in detail. It has been observed that substitution of 1 at.% Ga improved micro-hardness property of Ce-Cu-Al-Ga alloy. The value of yield strength of the materials is estimated with the help of hardness data and Meyer exponent. It has been found that this exponent decreases with respect to Ga substitution. © 2015 Elsevier B.V.